1999
DOI: 10.1073/pnas.96.15.8790
|View full text |Cite
|
Sign up to set email alerts
|

How can we boost IQs of “dull children”?: A late adoption study

Abstract: From 5,003 files of adopted children, 65 deprived children, defined as abused and͞or neglected during infancy, were strictly selected with particular reference to two criteria: (i) They were adopted between 4 and 6 years of age, and (ii) they had an IQ <86 (mean ‫؍‬ 77, SD ‫؍‬ 6.3) before adoption. The average IQs of adopted children in lower and higher socioeconomic status (SES) families were 85 (SD ‫؍‬ 17) and 98 (SD ‫؍‬ 14.6), respectively, at adolescence (mean age ‫؍‬ 13.5 years). The results show (i) a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(118 citation statements)
references
References 33 publications
7
103
0
7
Order By: Relevance
“…French national adoption studies, using a sibling-proband design, found that infant adoption had a positive effect on children's cognitive development, and that this process was positively correlated with the socio-educational background of the adoptive family [26,27]. The results were also replicated in a study of late adoptions (4-6 years) of neglected or abused children [28]. The educationally stimulating qualities of the adoptive families-and more specifically the socioeconomic prerequisites-are illustrated by the attenuation of differences of mean grade points between the adoptee groups and the majority population when socio-economic variables were also adjusted for (Table 3, The tests scores reflect functioning (at conscription) about 2 years after having finished ninth grade.…”
Section: Discussionmentioning
confidence: 82%
“…French national adoption studies, using a sibling-proband design, found that infant adoption had a positive effect on children's cognitive development, and that this process was positively correlated with the socio-educational background of the adoptive family [26,27]. The results were also replicated in a study of late adoptions (4-6 years) of neglected or abused children [28]. The educationally stimulating qualities of the adoptive families-and more specifically the socioeconomic prerequisites-are illustrated by the attenuation of differences of mean grade points between the adoptee groups and the majority population when socio-economic variables were also adjusted for (Table 3, The tests scores reflect functioning (at conscription) about 2 years after having finished ninth grade.…”
Section: Discussionmentioning
confidence: 82%
“…It cannot be known for certain what the IQ scores of the adoptees would have been had they not been adopted, but they might have been somewhat lower. IQ gains as large as 19.5 have been found among children adopted by high SES families at ages 4-6 and who had experienced abuse or neglect (Duyme, Dumaret, & Tomkiewcz, 1999). A recent meta-analysis showed that adopted children's IQ scores exceeded those of their non-adopted biological siblings and peers who remained with their birth families or in institutional care (Van Ijzendoorn, Juffer, & Poelhuis, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Case, Lubotsky, and Paxson (2002) found that the association between low SES and children's health outcomes was closely similar in biological and adoptive families (unfortunately the findings are reported rather briefly without adequate detail). The inference (as in the Duyme, Dumaret, & Tomkiewicz, 1999, study dealing with IQ on the dependent variable-see below) is that some form of causal environmental effect was operative. The adoptee design, however, requires specific attention to the possibility of selective placement.…”
Section: Adoptionmentioning
confidence: 99%